The Anatomy of Anomalies in the Swedish Stock Market (Global Journal of Management and Business Research, 2019)
The previous literature documents stock market anomalies that challenge the Efficient Market Hypothesis (EMH), such as the January effect, weekend effect, ex-right day effect, exdividend effect, momentum, and reversal. In this paper, we provide additional international evidence on the existence of these anomalies in the Sweden stock market by using a unique panel dataset from 1912 to 1978. Our findings are important for understanding both the Sweden stock market and the Efficient Market Hypothesis (EMH).
Keywords: anomalies; efficient market hypothesis; seasonality; event study; economic history